An Efficient Emergency Message Forwarding Technique with Improved Rebroadcast Suppression for VANETs - Karimulla Basha, S; N. Shankar, T (International Journal of Engineering and Technology, 2018)
Vehicle Ad Hoc networks are important because they can provide communication for moving vehicles without the need of infrastructural services being deployed on the road. To avoid drastic results of accidents on highways the moving vehicles need to be aware of the traffic situation by sending emergency messages using the wireless broadcast channel. The efficiency of such methods implemented to forward emergency messages needs to be elevated for their reliability by considering the vehicle density and broadcast nature of the wireless channel.Â Rebroadcast protocols need to perform with minimal delay and generate less traffic in terms of duplicated emergency messages. The current paper studies the use of zone based broadcast suppression method to establish its prominence in reducing congestion.Â Â